Aplicación web para el registro de consultas y manejo de historial clínico de los pacientes del patronato municipal del cantón Bolívar - Andrade Alcívar, Juan Gabriel (2013)
In order to improve the query log and management of medical records of patients in the Canton Municipal Bolivar implemented a web application on the official website of this institution. For this purpose it was necessary to know all the information that manipulated the entity through an analysis it was determined that these were made by hand, so that the creation of the aforementioned application served people working in the administration área the institution and informative way for users receiving care. Methods were used inductive-deductive scientific research, which allowed us to observe and detect how they were managed all records. Also applied techniques such as interviews and observation, which were very useful at the time to meet the objectives. The authors found it necessary to use the computer method OOHDM (Object - Oriented Hypermedia Design Method) which through its various phases help to perform work in an orderly manner allowing it to meet customer requirements. We used web development tools like PHP latest MySQL 5.2.5 and 5.5.8. Then they were tested for validation by interview for staff which confirmed that the application was created to meet the requirements and time tests confirmed the optimization processes of the same in the Municipal office of the county under Bolivar.